If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 7) + -6 = 9 + -2(x + 9) Reorder the terms: 9(7 + x) + -6 = 9 + -2(x + 9) (7 * 9 + x * 9) + -6 = 9 + -2(x + 9) (63 + 9x) + -6 = 9 + -2(x + 9) Reorder the terms: 63 + -6 + 9x = 9 + -2(x + 9) Combine like terms: 63 + -6 = 57 57 + 9x = 9 + -2(x + 9) Reorder the terms: 57 + 9x = 9 + -2(9 + x) 57 + 9x = 9 + (9 * -2 + x * -2) 57 + 9x = 9 + (-18 + -2x) Combine like terms: 9 + -18 = -9 57 + 9x = -9 + -2x Solving 57 + 9x = -9 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 57 + 9x + 2x = -9 + -2x + 2x Combine like terms: 9x + 2x = 11x 57 + 11x = -9 + -2x + 2x Combine like terms: -2x + 2x = 0 57 + 11x = -9 + 0 57 + 11x = -9 Add '-57' to each side of the equation. 57 + -57 + 11x = -9 + -57 Combine like terms: 57 + -57 = 0 0 + 11x = -9 + -57 11x = -9 + -57 Combine like terms: -9 + -57 = -66 11x = -66 Divide each side by '11'. x = -6 Simplifying x = -6
| -n-2=3 | | 3/5t-1/10t=t-5/2 | | 20m=80 | | -15x+5y=-2 | | 9.9+14.5(12.7-8.4)= | | 29x+40=10x+3 | | 42y-42y= | | 1/3(x-10)+2/4=x/5 | | x+31/2=41/2 | | 20-0.14x=18.32 | | 6(2x+8)=(3x-6) | | 6(9+4x)=-18solve | | 20+14.32=18.32 | | (x^2)+6x+3=0 | | 18+a=-8 | | 8x+6=5+9 | | 20-14.32x=18.32 | | m+7=10 | | -18+a=8 | | 10x^2-85x-45=0 | | (x^3)+(6x^2)+3x-10=0 | | (7x+b)=4(x+2c+b) | | 6y-8=5y-1 | | 6w-36=15w | | -3+-2= | | 3x^2+3=366 | | 10x-100=6x+20 | | n+11=12 | | 7y+8=5y-1 | | 7.5x+3y=19.5 | | 31b=-434 | | 0.25-0.5(x-3)=-0.25(5-x) |